Does roasting temperature and storage options of Macadamia nuts (Macadamia intergrifolia) affect nutritional and sensorial properties? - Ngwenyama, Patrick; Nyamuronda, Ottilia; Majachani, Kudzai; Benhura, Chakare; Mubayiwa, Macdonald (International Journal on Food, Agriculture and Natural Resources, 2024)
Macadamia nuts are a largely untapped potential source of nutrients, income, and livelihoods. There is low utilisation of this crop due to palatability issues and storability challenges. There is limited information on the effects of different processing methods such as roasting on palatability, nutrient retention and subsequent stability during storage of the nuts. This study investigated the effects of dry roasting macadamia nuts at different temperatures and their subsequent storage using different storage options on the nutritional and sensorial properties.  The nuts were dry-roasted for 25 minutes at three different temperature regimes: 150, 160and 170 oC, and were tested for nutritional content, antioxidant activity and peroxide value. Sensorial evaluation was conducted to determine the acceptability of the dry-roasted nuts. The nuts roasted at 160 oC were the most acceptable in terms of sensorial qualities. These were then stored under three different storage conditions, [open storage (control); plastic containers and glass containers] for 3 months. Samples were collected at 2-week intervals and analysed for proximate composition, peroxide value, and sensorial properties. Results showed that an increase in roasting temperature of macadamia nuts from 150 to 170 oC resulted in a significant increase (p<0.05) in ash, crude fat, peroxide value, and moisture content, while crude protein and carbohydrates significantly decreased. Roasting macadamia nuts at 170 °C significantly reduced their nutritional quality, while roasting at 150 and 160 °C retained the nutrients. Glass jars retained nutrients and organoleptic properties as compared to open storage and plastic containers where deterioration started after two and six weeks, respectively. Dry roasting of macadamia nuts is a viable way of value addition, and storage in glass jars is recommended for long-term storage.